Perlindungan Hukum Pasien Gawat Darurat Terhadap Jasa Pelayanan Kesehatan Di Rumah Sakit - Budiyono, Budiyono (Jurnal JURISTIC, 2024)
In modern times, access to quality healthcare, especially in emergency situations, is crucial. However, the implementation of legal protection for emergency patients in Indonesian hospitals faces several challenges. This study employs a descriptive normative legal research approach to analyze existing regulations and identify implementation obstacles. Through qualitative analysis, it was found that inadequate medical facilities, shortage of competent medical personnel, and poor regulation enforcement hinder optimal healthcare delivery. Strategies such as infrastructure investment, training programs, and regulatory compliance monitoring are proposed to address these challenges. Ensuring equitable distribution of medical resources between urban and rural areas is vital. Improving legal protection for emergency patients requires coordinated efforts from stakeholders and government intervention. Enhancing awareness, training, and enforcement mechanisms is imperative to safeguard patients' rights and improve healthcare quality.